Pengembangan Minat Studi Lanjut: Sosialisasi Strategi Masuk Perguruan Tinggi Negeri dan Simulasi Tryout Berbasis CAT (Computer Assisted Test) - Rasmiyana; Satika Dewi, Putri; Fahmi Brillyansyah, Degita; Ihsan Alfarizi, Muhammad; Mualimin, Lulus (Insan Kreasi Media, 2024)
Community service activities themed Socialization of State/Private University Entrance Strategy and CAT (Computer Assisted Test) Based Tryout Simulation were held at MA Al Ishlah Jenggawah, Jember. The purpose of this service is to improve the understanding, motivation, and readiness of grade XII students in continuing their education to college using the Lecture socialization and simulation method which is divided into 3 stages, namely preparation, implementation, and evaluation. The programs implemented include socialization of college selection pathways, effective learning strategies, scholarship information, and CAT-based Tryout simulations. The evaluation results showed a 130% increase in students' understanding of college selection pathways, from 1.98 on a scale of 5 (pre-test) to 4.56 on a scale of 5 (post-test). The Tryout Simulation provided real experience in facing technology-based exams, although the average score of 756 indicated the need for more intensive assistance. As many as 87% of students considered this activity useful in building self-confidence to continue their education to a higher level. This activity has a positive impact on preparing students academically and strengthening synergy between schools and organizers. For sustainability, it is recommended to hold periodic simulations, form independent study groups, and provide CAT devices in schools to support students' preparation in choosing a college.